Resistance theory and constitutionalism in Iran - Mohammad Reza Tajik; Aref Masoudi (رهیافتهای سیاسی و بین المللی)
Throughout the centuries, Iranians have tested various forms of resistance to dictatorship, such as assassination, armed uprising, revolution, and types of negative resistance. But during the constitutional movement when Iranain intellectuals attained the modern knowlages of society and politics, a new understanding about the problem and concept of resistance emerged. Historically, this new concept of resistance, of centuries before the constitutional movement of Iran, initially emeraged among the Christian sects opposed to the plenitude of divine power of the pope, and later against the European absolute monarchies, and was generally the result of theoretical efforts of the Protestant writers and proponents of constitutional monarchies. Such resistance, which can be called “resistance through legal processes”, is based on a principle depicted in constitutions that points out whenever a ruler or prince tries to dissolve the initial contract, then the people appeal to violence and they will have the right to resist him. This principle, as a significant constraint in the constitutions and fundamental laws, was the basis of what was called Resistance Theory in the modern political thought. In the course of the efforts of Iranian intellectuals to establish the rule of law and to explain the principles of constitutionalism, and especially during the period of “Estebdad e Sagheir”, the new understanding of the concept of resistance has been addressed in a few political and legal treatises. Since there has not been a comprehensive research on this aspect of the literature of resistance, especially during the constitutional movement of Iran, the paper is trying to discuss it.